Efeito de uma fosfolipase A2 básica isolada da peçonha de Bothropoides pauloensis (Bothrops pauloensis) sobre formas promastigota de Leishmania (Leishmania) amazonensis - Nunes, Débora Cristina de Oliveira (2011)
CHAPTER 2: Leishmaniasis is a group of diseases caused by protozoa of Leishmania genus. The currently available treatment for this disease presents high toxicity and cost, parasite resistance, and difficulties of healing. In this sense, the development of new strategies for treatment of leishmaniasis is indispensable and snake venoms appear as an important natural source of pharmacologically active biomolecules. The aim of this study was assess effects of a phospholipase A2 (BnSP-7) catalytically inactive, from Bothropoides pauloensis snake venom, on Leishmania (Leishmania) amazonensis. BnSP-7 presented activity against promastigote forms of parasite, both MTT assay, with percentage of cell viability around 60% to 200μg/mL of toxin, and growth curve, inhibiting 60-70% of parasite proliferation at concentrations of 50-200 μg/mL of toxin after 72h of treatment. Ultrastructural studies in promastigotes treated with BnSP-7 revealed mitochondrial swelling, nuclear alteration, vacuolization, acidocalcisomes presence, multiflagelar aspect and blebbing effect in plasma membrane. SDS-PAGE preliminary analysis showed that toxin seems to alter the parasite protein profile. Finally, BnSP-7 interfered with infective capacity of promastigote in murine peritoneal macrophages, causing statistically significant reductions (p < 0.05) of approximately 20-30% for toxin concentrations tested (25-200 μg/mL). Culture supernatants of infected macrophages for 72h with toxin treatedparasites presented increased production of TNF-α, reduction of IL-10 and slight increase of nitric oxide. These data suggest that the BnSP-7 is an important tool for discovery of new targets in the parasite that can be exploited for development of new drugs for leishmaniasis treatment.